Influência dos opioides exógenos na resposta inflamatória aguda no período perioperatório de cirurgia oncológica - Titon, Odirlei João (2021)
Opioids are classically used for analgesia and anesthesia both as adjuvants in general anesthesia and in spinal anesthesia (intrathecal) and epidural. There is evidence that these drugs interfere with the activation of immune cells, angiogenesis and cytokine release, and as they can affect the clinical course of cancer, they should be avoided in cancer patients. However, there are still doubts about the real benefits of opioid-free anesthesia. This work proposes to evaluate changes in the cellular and humoral immune response due to the use of opioids in the immediate pre- and postoperative period in patients with gastrointestinal, genitourinary, lung, breast and retroperitoneum neoplasms. It is a prospective preclinical trial, randomized for the use or not of opioids in the anesthetic technique, performed at the Cancer Hospital of Francisco Beltrão (CEONC). The patients were allocated into two groups with the aid of the electronic random number table: OP group, which received more epidural general anesthesia with the use of exogenous opioids, and the OF group, which received more epidural general anesthesia without opioid - opioid free. The OF group did not receive opioid analgesia at any time between collections, and other analgesics, such as dipyrone, paracetamol, non-steroidal antiinflammatory drugs, clonidine and lidocaine, were administered, unless contraindications. 47 adults, of both sexes, diagnosed with cancer in the aforementioned topographies, with physical status P1, P2 and P3 by the ASA (American Society of Anaesthesiologists) classification, included for elective surgery to remove the tumor at the Surgical Center of CEONC from July 2019 to October 2020. In the peripheral blood samples, comparative analyzes were performed between pre and post-anesthesia samples of the levels of cytokines interleukin 4 (IL-4), interleukin 12 (IL-12), interleukin 17 (IL-17), tumor necrosis factor alpha (TNFα) and lipoperoxidation profile as indicative of oxidative damage. All data collected were entered into an electronic spreadsheet and the statistical analysis of the association of sociodemographic data was performed using the Chi-square test of independence, followed by the adjusted residual post-test. For each cytokine, the ANOVA test for repeated measures was applied, followed by the Tukey-HSD test, in case of statistical significance (p <0.05). The association between the different variables was performed by the PERMANOVA test, followed by the Principal Coordinate Analysis (PCoA). The descriptive analysis showed the profile of the patients, with a mean age of 60 years, predominantly gastrointestinal (n = 18) and genitourinary (n = 16). Comparing the two groups, there was significant consumption of IL-12 in the OF-Post group compared to the OF-Pre group, with no variation of the other cytokines in this or in the other groups. There was also a significant reduction in the production of lipoperoxides in the post-anesthesia groups, regardless of the use of opioids. These findings demonstrated the acute impact on the inflammatory response of the drugs used in anesthesia, which generate consumption of IL-12 and attenuation of the levels of oxidative damage in cancer patients.